Zero Mode Effect Generalization for the Electromagnetic Current in the Light Front: Fermion Case - Suzuki, Alfredo Takashi [UNESP]; Sales, Jorge Henrique; Santos, Gislan S. (Springer, 2015)
We investigate the effect of the gamma (+) term in the fermion propagator on the zero mode in a system composed of two free fermions propagating in a background field. For this purpose we use the technique of global propagators in the light front and current operator in order to obtain the electromagnetic current component J (-).